Faktor Yang Berhubungan Dengan Kejadian Hipertensi Pada Ibu Hamil Di Puskesmas Jumpandang Baru Makassar - Asmirah, Rika; Supardi, Nurjannah (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2024)
Hypertension in pregnancy is blood pressure reaching 140/90 mmHg or more that occurs during pregnancy. Pregnant women who experience hypertension often occur at a gestational age of over 20 weeks. Hypertension in pregnancy can cause morbidity/illness in pregnant women (including seizures. This study aims to determine the relationship between age, history of hypertension, exposure to cigarette smoke, parity, and pregnancy stress on the incidence of hypertension in pregnant women in the Jumpandang Baru health center working area. Research Objective: To determine the risk factors for hypertension in pregnant women in the Jumpandang Baru Community Health Center work area based on maternal age, history of hypertension, exposure to cigarette smoke, parity, and pregnancy stress. Research Method: This research used an observational research type with a cross sectional study design approach, the population in this study was 73 pregnant women. The sampling technique used was total sampling. Data collection was obtained using a questionnaire. Analysis of relationships used the chi square test. Research Results: This shows that 38 people (53.4%) had hypertension, while 35 people (46.6%) did not have hypertension. Statistical test results showed that age (p=0.000), history of hypertension (p=0.004), exposure to cigarette smoke (p=0.431), parity (p=0.626) and pregnancy stress (p=0.007). Conclusion: that there is a relationship between age, history of hypertension, and pregnancy stress with the incidence of hypertension in pregnant women, while there is no relationship, namely exposure to cigarette smoke and parity with the incidence of hypertension in pregnant women in the Jumpandang Baru Makassar Health Center working area. Thus, pregnant women suffer Hypertension during pregnancy is expected to continue to control one's health, one of which is blood pressure that remains normal.